Key business analytics : the 60+ business analysis tools every manager needs to know - Marr, Bernard (Pearson Education, 2016)
Key Business Analytics will help managers apply tools to turn data into insights that help them better understand their customers, optimise their internal processes and identify cost savings and growth opportunities.